Burden of Ileal Perforations Among Surgical Patients Admitted in Tertiary Care Hospitals of Three Asian countries: Surveillance of Enteric Fever in Asia Project (SEAP), September 2016–September 2019. (1st December 2020) - Qazi, Saqib H; Yousafzai, Mohammad T; Saddal, Nasir S; Dehraj, Irum F; Thobani, Rozina S; Akhtar, Afshan; Syed, Jamal R; Kazi, Abdul M; Hotwani, Aneeta; Rahman, Najeeb; Mehmood, Junaid; Andrews, Jason R; et al.
Abstract: Background: Typhoid fever is caused by Salmonella enterica subspecies enterica serovar Typhi ( S . Typhi) and can lead to systemic illness and complications. We aimed to characterize typhoid-related ileal perforation in the context of the population-based Surveillance of Enteric Fever in Asia Project (SEAP) in Bangladesh, Nepal and Pakistan. Methods: Between September 2016 and September 2019, all cases of nontraumatic ileal perforation with a clinical diagnosis of typhoid were enrolled from 4 tertiary care hospitals in Karachi, 2 pediatric hospitals in Bangladesh, and 2 hospitals in Nepal. Sociodemographic data were collected from patients or their caregivers, and clinical and outcome data were retrieved from medical records. Tissue samples were collected for histopathology and blood cultures where available. Results: Of the 249 enrolled cases, 2 from Bangladesh, 5 from Nepal and 242 from Pakistan. In Pakistan, most of the cases were in the 0–15 (117/242; 48%) and 16–30 (89/242; 37%) age groups. In all countries, males were most affected: Pakistan 74.9% (180/242), Nepal 80% (4/5), and Bangladesh 100% (2/2). Blood culture was done on 76 cases; 8 (11%) were positive for S . Typhi, and all were extensively drug resistant (XDR) S . Typhi. Tissue cultures was done on 86 patients; 3 (3%) were positive for S . Typhi, and all were XDR S . Typhi, out of 86 samples tested for histopathology 4 (5%) revealed ileal perforation with necrosis. Culture or histopathology confirmed total 15 (11%) enteric fever cases with ileal perforation are similar to the clinically diagnosed cases. There were 16/242 (7%) deaths from Pakistan. Cases of ileal perforation who survived were more likely to have sought care before visiting the sentinel hospital ( P = .009), visited any hospital for treatment ( P = .013) compared to those who survived. Conclusions: Although surveillance differed substantially by country, one reason for the higher number of ileal perforation cases in Pakistan could be the circulation of XDR strain of S . Typhi in Karachi.